Diagnosis pitfall of interstitial pregnancy: a case report of a term pregnancy with abnormal placentation - Fatemeh Sadat Najib; Homeira Vafaei; Amin Abolhasan Foroughi; Niloofar Namazi (BMC, 2021)
Abstract Background Interstitial Pregnancy (IP) is a lethal condition due to high risk of sudden onset massive hemorrhage. Such conditions are managed as soon as diagnosed almost in the first trimester. There are a few case reports of IP conditions terminated after the second trimester. Herein, we introduce a term interstitial pregnancy complicated by abnormal placentation. Case presentation In this case report, we introduce a 32-year-old lady, primigravida, with an undiagnosed IP that was in her 38 weeks of gestational with placenta increta. She developed with perforated IP presenting with acute abdomen and internal bleeding at 26 weeks of gestational age. However, with a misdiagnosis impression, she got stable in operation room. Then, the pregnancy continued till 36 weeks of gestational age that was misdiagnosed with cervical cancer in prenatal work-ups. Finally, during elective cesarean section at 38 weeks, an IP with placenta increta (placenta evading from the serosa to the myometrium of the uterus) was observed. The baby was healthy with no obvious anomaly or morbidity. Conclusions Physicians should be aware to detect IP in all trimesters and pay attention to the coexisting complications such as placenta accreta to manage them more accurately.